2022
DOI: 10.1016/j.aninu.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-D-glucosamine improves the intestinal development and nutrient absorption of weaned piglets via regulating the activity of intestinal stem cells

Abstract: Early weaning in piglets can cause a series of negative effects. This causes serious losses to the livestock industry. N -Acetyl-D-glucosamine (D-GlcNAc) plays an important role in regulating the homeostasis of the intestine. This study aimed to investigate the effects of D-GlcNAc on the growth performance and intestinal function of weaned piglets. Twenty-four weaned piglets ([Yorkshire × Landrace] × Duroc, 6.58 ± 0.15 kg, n = 8) at 21 d old were fed 3 diets supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The higher the villus height, the larger the surface area available for nutrient absorption ( 47 ). A shallower crypt depth indicates more mature cells ( 48 ) with superior ability to digest and absorb beneficial compounds ( 49 ). The V/C ratio reflects the comprehensive intestinal nutrient absorption capacity and the degree of development ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher the villus height, the larger the surface area available for nutrient absorption ( 47 ). A shallower crypt depth indicates more mature cells ( 48 ) with superior ability to digest and absorb beneficial compounds ( 49 ). The V/C ratio reflects the comprehensive intestinal nutrient absorption capacity and the degree of development ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the experiment demonstrated that, as temperature increased, the abundances of Bacteroides and N-acetyl-D-glucosamine initially decreased and subsequently increased. Intestinal homeostasis is significantly regulated by N-acetyl-D-glucosamine (Wang et al, 2022b). Roseburia possesses a complete genome and a core for the synthesis of amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The feed intakes were aggregated throughout the experiment, and the pigs were weighed monthly. The average daily feed intake (ADFI), average daily gain (ADG), and ratio of daily feed intake to daily gain (F/G) were calculated according to the methods recommended by Wang et al ( 16 ). After the experiment, one medium-weight Ningxiang pig was selected from each pen and euthanized according to Yan et al ( 17 ).…”
Section: Methodsmentioning
confidence: 99%